2022
DOI: 10.1007/s11046-022-00703-z
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Capitis in Children Younger than Two Years Old: A Retrospective Study and Treatment Recommendations

Abstract: Background: Tinea capitis (TC) is a dermatophytosis of the scalp and hair, which occurs less common in infants younger than two years of age, and the data of TC in this age group are still unknown.Objectives: We aimed to reveal the epidemiological, clinical and mycological characteristics of TC in infants.Methods: We retrospectively analyzed all reported cases of TC in infants in their rst two years of life from 1991 to 2022, by searching PubMed, Embase, Web of Science, CNKI, Wanfang and Weipu databases.Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…20 Tinea capitis and kerion can lead to long-term complications such as permanent scarring alopecia. 5 Arenas et al studied 19 patients with kerion and five showed scarring alopecia. 21 Also, other cases reported this due to delayed diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…20 Tinea capitis and kerion can lead to long-term complications such as permanent scarring alopecia. 5 Arenas et al studied 19 patients with kerion and five showed scarring alopecia. 21 Also, other cases reported this due to delayed diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp dermatophytosis, with or without abscess formation, should be considered as a differential diagnosis for any hair loss patches, particularly those with epidermal changes. Any delay in diagnosis and treatment may result in more extensive scalp involvement and lead to complications such as permanent hair loss 4,5 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations